NARASI KEKERASAN DAN RESISTENSI DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM (NARRATIVES OF VIOLENCE AND RESISTANCE IN THE NOVEL THE WOMAN WHO CRIED TO THE BLACK MOON) - Rakhyuni, Rakhyuni (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study examines the narrative of violence and resistance in the novel "The Woman Who Cried to the Black Moon" by Dian Purnomo. The novel portrays the struggle of the protagonist, Magi Diela, against the patriarchal system represented by the bride kidnapping tradition in Sumba. Using a qualitative approach and descriptive analysis, the study reveals that the violence experienced by women in the novel encompasses physical, psychological, and social dimensions. Magi Diela’s resistance, carried out physically, verbally, and socially, reflects the fight against gender-based violence. Her struggle results in significant impacts, both personally and socially, including bringing the perpetrators to justice and raising public awareness about the importance of protecting women. This research demonstrates that resistance against the patriarchal system requires courage, determination, and social support to achieve meaningful change. Penelitian ini mengkaji narasi kekerasan dan resistensi dalam novel “Perempuan yang Menangis kepada Bulan Hitam” karya Dian Purnomo. Novel ini menggambarkan perjuangan tokoh Magi Diela melawan sistem patriarki yang diwakili oleh tradisi kawin tangkap di Sumba. Dengan pendekatan kualitatif dan analisis deskriptif, penelitian ini menemukan bahwa kekerasan yang dialami perempuan dalam novel meliputi fisik, psikologis, dan sosial. Resistensi yang dilakukan Magi Diela, baik secara fisik, verbal, maupun sosial, mencerminkan bentuk perjuangan perempuan melawan kekerasan berbasis gender. Perjuangan Magi menghasilkan dampak signifikan, baik pada lingkup personal maupun sosial, termasuk membawa pelaku kekerasan ke pengadilan dan meningkatkan kesadaran masyarakat tentang pentingnya perlindungan terhadap perempuan. Penelitian ini menunjukkan bahwa perlawanan terhadap sistem patriarki memerlukan keberanian, keteguhan, dan dukungan sosial untuk menghasilkan perubahan yang berarti.